Prostate cancer extracellular vesicles mediate intercellular communication with bone marrow cells and promote metastasis in a cholesterol‐dependent manner. Issue 2 (31st December 2020) - Henrich, Stephen E.; McMahon, Kaylin M.; Plebanek, Michael P.; Calvert, Andrea E.; Feliciano, Timothy J.; Parrish, Samuel; Tavora, Fabio; Mega, Anthony; De Souza, Andre; Carneiro, Benedito A.; Thaxton, C. Shad
Abstract: Primary tumours can establish long‐range communication with distant organs to transform them into fertile soil for circulating tumour cells to implant and proliferate, a process called pre‐metastatic niche (PMN) formation. Tumour‐derived extracellular vesicles (EV) are potent mediators of PMN formation due to their diverse complement of pro‐malignant molecular cargo and their propensity to target specific cell types (Costa‐Silva et al., 2015; Hoshino et al., 2015; Peinado et al., 2012; Peinado et al., 2017). While significant progress has been made to understand the mechanisms by which pro‐metastatic EVs create tumour‐favouring microenvironments at pre‐metastatic organ sites, comparatively little attention has been paid to the factors intrinsic to recipient cells that may modify the extent to which pro‐metastatic EV signalling is received and transduced. Here, we investigated the role of recipient cell cholesterol homeostasis in prostate cancer (PCa) EV‐mediated signalling and metastasis. Using a bone metastatic model of enzalutamide‐resistant PCa, we first characterized an axis of EV‐mediated communication between PCa cells and bone marrow that is marked by in vitro and in vivo PCa EV uptake by bone marrow myeloid cells, activation of NF‐κB signalling, enhanced osteoclast differentiation, and reduced myeloid thrombospondin‐1 expression. We then employed a targeted, biomimetic approach to reduce myeloid cell cholesterol in vitro and in vivo prior to conditioning with PCa EVs. Reducing myeloid cell cholesterol prevented the uptake of PCa EVs by recipient myeloid cells, abolished NF‐κB activity and osteoclast differentiation, stabilized thrombospondin‐1 expression, and reduced metastatic burden by 77%. These results demonstrate that cholesterol homeostasis in bone marrow myeloid cells regulates pro‐metastatic EV signalling and metastasis by acting as a gatekeeper for EV signal transduction.